2019
DOI: 10.1542/hpeds.2019-0061
|View full text |Cite
|
Sign up to set email alerts
|

Volume Versus Mass Dosing of Epinephrine for Neonatal Resuscitation: A Randomized Trial

Abstract: BACKGROUND: Intravenous epinephrine for neonatal resuscitation requires weight-based calculations. Epinephrine is available in 2 different concentrations, increasing the risk of dosing errors. Expert panels have conflicting recommendations for the ordering method. The Neonatal Resuscitation Program recommends the volume (milliliters per kilogram) method, whereas the Institute for Safe Medication Practices recommends the mass (milligrams per kilogram) method. In this study, we aim to determine if the mass metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…On the basis of the frequency of errors in our previous study, we estimated that 100 participants would be required to identify this difference (a 5 .05; b 5 .8; P 1 [proportion 1] 5 .4 and P 2 [proportion 2] 5 .15). 10,12 Categorical data were compared by using Fisher' s exact tests. Continuous and ordinal data were compared by using Mann-Whitney U tests.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the basis of the frequency of errors in our previous study, we estimated that 100 participants would be required to identify this difference (a 5 .05; b 5 .8; P 1 [proportion 1] 5 .4 and P 2 [proportion 2] 5 .15). 10,12 Categorical data were compared by using Fisher' s exact tests. Continuous and ordinal data were compared by using Mann-Whitney U tests.…”
Section: Discussionmentioning
confidence: 99%
“…13 The frequency and nature of epinephrine dosing errors during simulated neonatal resuscitations were described in a previous study. 10 Using both mass (milligrams per kilogram) and volume (milliliters per kilogram) dosing methods, nurses made errors in 43% of neonatal epinephrine doses. As anticipated, this error rate was consistent with the error rate found in the control (no cognitive aid) group of the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A threefold difference between the lower (0.01 mg/kg) and upper (0.03 mg/kg) range of epinephrine doses with no clear recommendations on the optimal initial dose increases complexity and risk of error. [5][6][7] A recent retrospective study has shown that an initial low umbilical venous catheter (UVC) dose of 0.01 mg/kg necessitated repeated and escalating doses of epinephrine to achieve ROSC, resulting in high cumulative epinephrine doses (up to 0.13 mg/ kg). 8 We have, therefore, chosen to study the lower-range and higher-range dose of epinephrine as recommended by the Neonatal Resuscitation Programme (NRP).…”
Section: Introductionmentioning
confidence: 99%